1979
DOI: 10.1002/jss.400120208
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of metastatic heterogeneity by short‐term in vivo passage of a cloned transformed cell line

Abstract: An experimental system for the study of metastasis has been developed using an epithelioid cell line of hepatic origin which had previously been chemically transformed in vitro. These metastatic cells were studied in the syngeneic rat strain. The cloned parent cell line metastasizes only to the lungs following intravenous, subcutaneous, or intraperitoneal injection. The metastatic phenotype is stable during in vitro passage, and subclones from the parent clone have a metastatic capacity statistically similar t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
23
0

Year Published

1981
1981
1985
1985

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…1). Isolation and comparison of tumor cell clones (2)(3)(4)(5)(6) or sublines (7)(8)(9)(10)(11)(12)(13)(14)(15) that have different metastatic abilities offers new opportunities for correlating specific cellular alterations with the metastatic phenotype. The success of this approach will depend, however, on the stability of the metastatic phenotype in these subpopulations during serial passage in vivo or in vitro.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1). Isolation and comparison of tumor cell clones (2)(3)(4)(5)(6) or sublines (7)(8)(9)(10)(11)(12)(13)(14)(15) that have different metastatic abilities offers new opportunities for correlating specific cellular alterations with the metastatic phenotype. The success of this approach will depend, however, on the stability of the metastatic phenotype in these subpopulations during serial passage in vivo or in vitro.…”
mentioning
confidence: 99%
“…In other tumor systems, however, passage in vivo of cloned tumor lines led to a rapid emergence of diversity, yet the same tumor lines grown in parallel in culture remain stable (6,20). Apparently, host selection pressure could have been responsible for this phenomenon (6).…”
mentioning
confidence: 99%
“…Progressive growth of metastatic lesions is accompanied by emergence, within originally clonally homogeneous lesions, of variant tumor cells with altered metastatic properties (intralesional clonal heterogeneity). By 40-45 days after initial arrest of injected tumor cells in the lung, 90% of the metastatic lesions are populated by cells with heterogeneous metastatic phenotypes.Studies in several laboratories have shown that malignant tumors contain subpopulations of cells that differ widely in their metastatic abilities (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). This cellular heterogeneity is believed to result from the formation of variant subpopulations of tumor cells with altered metastatic properties during progressive tumor growth (15).…”
mentioning
confidence: 99%
“…Studies in several laboratories have shown that malignant tumors contain subpopulations of cells that differ widely in their metastatic abilities (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). This cellular heterogeneity is believed to result from the formation of variant subpopulations of tumor cells with altered metastatic properties during progressive tumor growth (15).…”
mentioning
confidence: 99%
“…Both metastatic and threshold inoculum models have yielded evidence to support the idea that cloned tumors can generate detectable variants during growth in vivo (Talmadge et al, 1979(Talmadge et al, , 1981Chow and Greenberg, 1980;Chow et al, 1983) or in vivo and in vitro for some tumor lines (Cifone and Fidler, 1981). Attempts to correlate increased metastatic potential with increasing ability to generate drug-resistant variants, a relatively low frequency alteration, proved positive, suggesting that mutations may form the basis of some of the variants formed (Cifone and Fidler, 1981).…”
mentioning
confidence: 93%